“Preparing” and “Repairing” Public Debate: Organizational Learning of Promoters in Environmental and Energy Governance - Simard, Louis (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2005)
The deliberation experience, new imperative for public action (Blondiaux and Sintomer, 2002) produces some forms of learning that set in a new way the distribution of resources in punctual actors system that create infrastructure projects. If deliberative procedures could appear like moments for “metre à plat” values, ideas and solutions in a equilibrated, informed, respectful and transparency exchange, could we expect that it will suspend the power manifestations and the “rapports de force” in the pursuit of interests for stakeholders ? Analyzing the operation of environmental and energetic governance at the individual project level, from the promoter’s point of view, by looking at four extra-high-voltage (EHV) transmission line projects in France and Québec, and the consultation and deliberation procedures applied in each case, we argue that promoters learn better and quicker than the other stakeholders that are concerned by the large infrastructure projects. The radical imbalance of resources, experience and learning capacity among the actors tends to promote negotiation, before and after the public debate, with the actors considered relevant by the promoter, emptying the public debate of much of its content by leaving only the most antagonistic parties.